2017
DOI: 10.29267/mxjb.2017.2.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromium (VI) in aqueous solution by oat biomass (Avena sativa)

Abstract: Chromium (VI) removal capacity in aqueous solution by oat biomass was analyzed by the diphenylcarbazide method. Bioadsorption was evaluated at different pH values (1, 2, 3 and 4) and at different times. The effect of temperature in the range of 28 °C to 60 °C and the removal at different initial Cr (VI) concentrations of 200 to 1000 mg/L were also studied. The highest bioadsorption (100% with 100 mg/L of the metal and 1 g of biomass) was at 8 h, at pH of 1.0 and 28 °C. With regard to temperature, the highest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…With respect to the optimum incubation time and pH for metal removal by N. tabacum biomass, the highest removal was to 24 h and pH 2.0. About, the A. sativa biomass, eliminate 100 mg/L of chromium (VI) after 8 h, pH 1.0, 1 g of biosorbent, and 28 °C [9], with D. rotundata, the removal of hexavalent chromium, was of 325.88 mg/L, in 200 min, pH 2.0 (0.03 g de biosorbent) [12], for E. Officinalis (2.5 g/L of biomass) was report a capacity Universal Journal of Green Chemistry of removal of 416 mg/L, in 100 min [13], with O. sativa L. there was a biosorption of 94.3 mg/L, pH 5.2, 2 h at 28 °C [14], and with the A. cepa biomass, the removal was of 49 mg/L [50 mg/L of initial concentration of chromium (VI)] pH 1.0, 28 °C, and 0.5 g/L of biomass [18]. The differences founded in these conditions, could partly explain, by changes in the permeability of unknown origin, providing greater or lesser exposure of the functional groups of the cell wall of the biomass analysed [8,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the optimum incubation time and pH for metal removal by N. tabacum biomass, the highest removal was to 24 h and pH 2.0. About, the A. sativa biomass, eliminate 100 mg/L of chromium (VI) after 8 h, pH 1.0, 1 g of biosorbent, and 28 °C [9], with D. rotundata, the removal of hexavalent chromium, was of 325.88 mg/L, in 200 min, pH 2.0 (0.03 g de biosorbent) [12], for E. Officinalis (2.5 g/L of biomass) was report a capacity Universal Journal of Green Chemistry of removal of 416 mg/L, in 100 min [13], with O. sativa L. there was a biosorption of 94.3 mg/L, pH 5.2, 2 h at 28 °C [14], and with the A. cepa biomass, the removal was of 49 mg/L [50 mg/L of initial concentration of chromium (VI)] pH 1.0, 28 °C, and 0.5 g/L of biomass [18]. The differences founded in these conditions, could partly explain, by changes in the permeability of unknown origin, providing greater or lesser exposure of the functional groups of the cell wall of the biomass analysed [8,29].…”
Section: Discussionmentioning
confidence: 99%
“…Those materials include microorganisms, like bacteria, mushrooms, algae, waste and lignocellulosic material, and others, like shellfish, which can be removal CO2 from the atmosphere [5][6][7], and several studies have shown that metal bonding occurs especially through a chemical functional group (carboxyl and hydroxyl groups) [8]. Some reports in the literature that use low-cost materials for the elimination, reduction and/or removal of this metal are: oat biomass (Avena sativa) [9], tella residue and pea seed shell (Pisum sativum) [10], avocado seed [11] inert biomasses of Dioscorea rotundata and Elaeis guineensis [12], amla wood sawdust (Emblica officinalis) [13], rice husk [14], Arachis hypogea husk [15], Heinsia crinita seed coat biomass [16], bagasse [17], onion waste [18], and modified biomass of rice husk (Oriza sativa L.) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Those materials include microorganisms, like bacteria, mushrooms, algae, waste and lignocellulosic material, and others, like shellfish, which can be removal CO2 from the atmosphere (Pertile et al, 2021;Moore, 2020;Petros et al, 2021), and several studies have shown that metal bonding occurs especially through a chemical functional group (carboxyl and hydroxyl groups) (Boakye et al, 2022). Some reports in the literature that use low-cost materials for the elimination, reduction and/or removal of this metal are: oat biomass (Avena sativa) (Pacheco-Castillo et al, 2017), tella residue and pea seed shell (Pisum sativum) (Kebede et al, 2022), avocado seed (Mejía-Barajas, 2020), inert biomasses of Dioscorea rotundata and Elaeis guineensis (Villabona-Ortíz et al, 2022), amla wood sawdust (Emblica officinalis) (Kushwaha & Chakraborty, 2021), rice husk (Khalil et al, 2021), Arachis hypogea husk (Bayuo et al, 2020), Heinsia crinita seed coat biomass (Dawodu et al, 2020), bagasse (Kumar et al, 2020), onion waste (Prokopov et al, 2022), and modified biomass of rice husk (Oriza sativa L.) (Rodríguez-Pérez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%